Psychology of Breastfeeding: From Self Narration to Digital Technology - Ade Iva Murty; Safira Binar Anjani (Jurnal Online Psikogenesis, 2021)
Background: Breastfeeding has been a very precious source for the development of infants and children. Generally, most of the studies about breastfeeding come from a medical knowledge point of view. However, the process of sustaining exclusive breastfeeding is not an easy task for a mother. As breastfeeding involves a mother's decision-making process, the study explores how mothers live in a megapolitan area, preserving exclusive breastfeeding until baby 6 months old and partially continued up to 2 years old. Psychology emphasizes individual (psychological) and macro factors which have a significant role in enabling exclusive breastfeeding.   Methodology: The study methodology was qualitative with case study type. Methods of data collection were an in-depth interview and on-the-spot interview observation. We have interviewed 4  participants. All of them are urban mothers (women live in megapolitan areas of Jakarta Greater Area or JABODETABEK). Age ranges from 20 to 40 years old, with at least an experience of exclusive breastfeeding and the child’s age currently not more than 12 years old. 2 out of 4 participants are working mothers, who have to strive every day between domestic and work domain.Result: All 4 research subjects are typically kind of “pejuang ASI” (breastfeeding warrior), a term used for representing a maternal woman who fights hard to breastfeed, as the best nutrition for a baby. It was shown that psychological processes of preserving exclusive breastfeeding of an urban mother significantly reflect the role of self-narration around the perception of breastfeeding as part of “natural mother” schema and how digital technology helps a mother to get more support and solve breastfeeding and baby’s problems.Conclusion:  First Mother’s schema about breastfeeding and attachment to the baby are important to motivate her to maintain exclusive breastfeeding. we need to know how her schema about breastfeeding and her attachment to the baby.  Second, it is important to identify her skills and knowledge on using digital technology diligently, for a more productive and comfortable process of delivering the best nutrition for the baby.